Potensi Pigmen Pewarna Alami pada Corak Warna Lipa Sabbe sebagai Sumber Belajar IPA - Nur Yusaerah; Syahidah Rahmah; Mujibur Rahman (Lembaga Pengembangan Kinerja Dosen, 2022)
Along with the growing public awareness of personal and environmental health, lipa sabbe products with natural colors are increasingly popular. Natural dyes are advantageous because they do not need to be imported, are safe for human health during the manufacturing process, do not pollute the environment, and are safe. Although synthetic dyes are easier to use, they are harmful to health, produce hazardous waste, pollute the environment, and are made from imported materials. This study aims to determine the types of plants that can be used as natural dyes for lipa sabbe. Qualitative methods with literature studies sourced from journals, books, or other related scientific articles are used in this research. The results showed that natural dyes in lipa sabbe became one of the Science Learning Resources with natural dyes including extracts from cocoa shell waste, coconut fiber waste, oil palm shell waste, rambutan peel waste, mangosteen peel waste, guava leaf waste, mango leaf waste and avocado leaf waste is plantation waste that can be used as a natural lipa sabbe dye. The pigments in this material produce yellow, reddish brown, gray, and black colors. Keywords: , ,.